LEGAL RESPONSIBILITY OF PRODUCT PROMOTION INFLUENCERS THAT ARE HARMING BUYERS FROM THE PERSPECTIVE OF UNLAWFUL ACTS - Khairul Imam Batubara; Ismail Koto (Inspiring Law Journal, 2025)
The rapid development of information and communication technology has made social media a primary means of promoting products and services. Influencers play a strategic role in shaping public opinion and broadly influencing consumer purchasing decisions. However, behind the effectiveness of such promotions, there is the potential for misleading, non-transparent, or inconsistent promotional practices. This situation has the potential to cause losses, both material and immaterial, for buyers as consumers. This phenomenon raises legal issues regarding the extent of influencers' legal responsibility for their product promotions, as well as the forms of legal protection available to consumers who suffer losses. This study aims to analyze the legal regulations related to product promotion activities by influencers on social media, examine the forms of legal liability that can be imposed from the perspective of unlawful acts, and identify legal protection mechanisms for consumers who suffer losses due to misleading promotions. The research method used is normative legal research with a descriptive-analytical nature. This approach is carried out by examining relevant laws and regulations, particularly the Civil Code, the Consumer Protection Law, and regulations related to digital promotional activities. The research data sources include primary legal materials in the form of laws and court decisions, secondary legal materials in the form of legal doctrine and literature, and secondary data studies related to digital promotion practices and consumer protection issues. The results of the study indicate that influencers can be held legally accountable if proven to have committed unlawful acts through misleading, dishonest, or negligent product promotions. Article 1365 of the Civil Code serves as the primary basis for assessing the existence of elements of unlawful acts, which include actions, errors, losses, and the causal relationship between the promotion and the losses experienced by consumers. Legal protection for consumers needs to be carried out comprehensively through civil lawsuits, alternative dispute resolution such as mediation, increasing digital literacy and education, and monitoring promotional content on social media. This study emphasizes the importance of the principles of transparency, honesty, and social responsibility in digital marketing practices to create equitable consumer protection.